Ultrathin tri-band reflective cross-polarization artificial electromagnetic metasurface. Issue 10 (2nd July 2020) - Yang, Zhengyi; Yu, Shixing; Kou, Na; Long, Fei; Ding, Zhao; Zhang, Zhengping
Abstract : A high-efficiency tri-band artificial electromagnetic (EM) polarization manipulating metasurface is proposed, which is employing two metal rectangle rings composed of a single-layer reflectance surface. There are three frequency bands generated by the artificial EM polarization manipulating metasurfaces, with 3-dB bandwidth at 9.10–12.40, 15.55–23.80 and 24.71–30.00 GHz, and the relative bandwidth is 30.7%, 41.9% and 19.4%, respectively. The polarization converter ratio of the polarization manipulating metasurfaces is great than 90% at 9.8–12.2, 19–22.6, and 24.9–29.5 GHz, respectively. There are five resonance frequencies at 10.5, 11.8, 20.9, 25.7 and 28.3 GHz, where the polarization converter ratio is almost reached 100%. Equivalent circuit and surface current distributions reveal that the coupling results from the strong electric and magnetic resonances between the top surface and bottom ground. Experimental results of the prototype are basically consistent with the simulation results, which clearly show that the metasurfaces have multiband characteristics and higher efficiency.